Cytotoxic constituents from the bark of Aglaia eximia (Meliaceae) - Awang, Khalijah; Harneti, D.; Supriadin, A.; Ulfah, M.; Safari, A.; Supratman, U.; Hayashi, H. (Elsevier, 2014)
The new stigmastane steroid,3,4epoxy-(22R,25)-tetrahydrofuran-stigmast-5-en (1), along with two known triterpenoids (2–3) and two known steroids (4–5) were isolated from the stem bark of Aglaia eximia. The chemical structures of the new compound were elucidated on the basis of spectroscopic data. All of the compounds were tested for their cytotoxic effects against P-388 murine leukemia cells.Compounds 1–5 showed cytotoxicity against P-388 murine leukemia cells with IC50 values of 11.42, 4.26, 29.10, 45.96, and 52.09 mg/mL, respectively.